A novel hybrid energy system for hydrogen production and storage in a depleted oil reservoir. (17th May 2021) - Song, Hongqing; Guo, Honghao; Wang, Yuhe; Lao, Junming; Zhu, Huayin; Tang, Ligen; Liu, Xuan
Abstract: Renewable and carbon free energy relates to the sustainable development of human beings while hydrogen production by renewables and hydrogen underground storage ensure the stable and economic renewable energy supply. A hybrid energy system combining hydrogen production by offshore wind power with hydrogen storage in depleted oil reservoirs was constructed along with a mathematical model where the Weibull distribution, Wind turbine power function, Faraday's law, continuity equation, Darcy's law, state equation of real gas, Net Present Value (NPV) and the concept of leveling were adopted to clarify the system characteristics. For the case of a depleted oil field in the Bohai Bay, China, the annual hydrogen production, annual levelized cost of hydrogen and payback period are 2.62 × 10 6 m³, CNY 34.6/kgH2 and 7 years, respectively. Sensitivity analysis found that the wind speed impacted significantly on system NPV and LCOH, followed by hydrogen price and stratum pressure. Highlights: A novel hybrid energy system for hydrogen production and storage was built. The hydrogen was produced by offshore wind while stored in the depleted reservoir. The H2 production and CO2 reduction were 2.6 × 10 6 m³ and 6.9 × 10 5 kg annually. The system NPV and payback period were CNY 1.1 × 10 8 and 7 years. Wind speed, H2 price and stratum static pressure impacted the most on system NPV.